Blood Lead and Cadmium Levels in Transfusion-Dependent Thalassemia Patients - Balqees Kadhim Hasan; Meaad Kadhum Hassan; Wasan Hameed Saud (Medical Journal of Babylon)
Background: The risk of heavy metal toxicity, including lead and cadmium, is high in individuals with diseases requiring multiple blood transfusions like thalassemia. Objectives: To evaluate blood lead levels and serum cadmium in transfusion-dependent thalassemia (TDT) patients and the impact of iron chelation therapy (ICT) on their levels. Materials and Methods: This case–control study involved 110 patients with TDT and 70 healthy individuals, their ages ranged from 4 to 37 years. Patients with TDT were subdivided into those on deferasirox (60 patients) and deferoxamine (50 patients). Blood samples were collected from all participants for complete blood counts of serum ferritin and iron. Serum cadmium and lead levels were estimated using an AA-7000 Atomic Absorption Spectrophotometer. Results: Mean hemoglobin level was significantly lower while serum iron and ferritin were significantly higher in TDT patients compared to the control group. Serum levels of lead and cadmium were not significantly different between healthy subjects and TDT patients, P > 0.05. Serum lead and cadmium levels were also not significantly different between patients on different iron chelators, P > 0.05. Pearson correlation did not reveal any significant correlation between lead (R* = 0.05 and 0.176) and cadmium (R* = -0.012 and -0.075) with each of serum iron and ferritin, respectively. Conclusions: Although serum levels of lead and cadmium were not significantly different between TDT patients and healthy individuals, the relatively high lead levels among studied participants need further studies to identify risk factors and to put an immediate action plan.